Static Performance Characteristics Of Vortex Rate Sensor (Journal of Engineering, 2012)
The vortex rate sensor is a fluidic gyroscope with no moving parts and can be used in very difficult conditions like radiation, high temperature and noise with minimum cost of manufacturing and maintenance. A vortex rate sensor made of wood has been designed and manufactured to study theoretically and experimentally its static performance .A rig has been built to carry out the study, the test carried out with three different air flow rates (100, 150, and 200 l/min).The results show that the relation between the differential pressure taken from the sensor pickoff points and the angular velocity of the sensor was linear.The present work involved theoretical and experimental study of vortex rate sensor static characteristics .Vortex rate sensor has been designed and manufactured with dimensions :- Radius of vortex chamber= 140 mm, Radius of sink tube rs= 4.5 mm, the pickoff hole diameter = 2mm, Height of vortex chamber b= 19 mm, Height of pickoff pipe h= 25 mm.